Mutations in GRK2 cause Jeune syndrome by impairing Hedgehog and canonical Wnt signaling. Issue 11 (14th October 2020) - Bosakova, Michaela; Abraham, Sara P; Nita, Alexandru; Hruba, Eva; Buchtova, Marcela; Taylor, S Paige; Duran, Ivan; Martin, Jorge; Svozilova, Katerina; Barta, Tomas; Varecha, Miroslav; Balek, Lukas; et al.
Abstract: Mutations in genes affecting primary cilia cause ciliopathies, a diverse group of disorders often affecting skeletal development. This includes Jeune syndrome or asphyxiating thoracic dystrophy (ATD), an autosomal recessive skeletal disorder. Unraveling the responsible molecular pathology helps illuminate mechanisms responsible for functional primary cilia. We identified two families with ATD caused by loss‐of‐function mutations in the gene encoding adrenergic receptor kinase 1 ( ADRBK1 or GRK2 ). GRK2 cells from an affected individual homozygous for the p.R158* mutation resulted in loss of GRK2, and disrupted chondrocyte growth and differentiation in the cartilage growth plate. GRK2 null cells displayed normal cilia morphology, yet loss of GRK2 compromised cilia‐based signaling of Hedgehog (Hh) pathway. Canonical Wnt signaling was also impaired, manifested as a failure to respond to Wnt ligand due to impaired phosphorylation of the Wnt co‐receptor LRP6. We have identified GRK2 as an essential regulator of skeletogenesis and demonstrate how both Hh and Wnt signaling mechanistically contribute to skeletal ciliopathies. Synopsis: This study identifies GRK2 as a regulator of human skeletogenesis. Loss of GRK2 deregulates the function of two major morphogens in the bone ‐ Hedgehog and canonical Wnt signaling, and manifests in autosomal recessive skeletal ciliopathy syndrome, asphyxiating thoracic dystrophy or Jeune syndrome. GRK2 loss leads to bone defects involving the proliferation and hypertrophic differentiation of chondrocytes in the growth plate cartilage, and sulfation of the cartilage extracellular matrix. GRK2 loss causes under‐phosphorylation of Smoothened and its exclusion from the cilia, and inhibits Hedgehog pathway. GRK2 loss inhibits canonical Wnt signaling through reduced LRP6 phosphorylation and Frizzled‐βArrestin2 interaction. Abstract : This study identifies GRK2 as a regulator of human skeletogenesis. Loss of GRK2 deregulates the function of two major morphogens in the bone ‐ Hedgehog and canonical Wnt signaling, and manifests in autosomal recessive skeletal ciliopathy syndrome, asphyxiating thoracic dystrophy or Jeune syndrome.